Human-centered strategies for sustainable firm growth through competitive advantage in the gypsum board industry in Indonesia - Sutanto Sutanto; Sri Widyastuti; Mombang Sihite (Jurnal Konseling dan Pendidikan, 2025)
The gypsum board industry in Indonesia faces significant challenges in sustaining firm growth amid market competition and dynamic business environments. This study aims to examine the influence of innovation, dynamic capabilities, and agile leadership on sustainable firm growth, with competitive advantage as a mediating variable and product life cycle as a moderating variable. A mixed methods approach was applied, combining quantitative data from 27 managerial respondents analyzed using mediation and moderation regression via SmartPLS, and qualitative data from in-depth interviews with two informants representing companies in growth and decline phases. The findings reveal that competitive advantage significantly mediates the relationship between strategic factors and sustainable firm growth. However, the product life cycle does not show a significant moderating effect. These results highlight the critical role of strengthening competitive advantage as a core strategy to achieve sustainable growth in Indonesia’s gypsum board industry.